1996
DOI: 10.2527/1996.7461240x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of physical form of feed, carbohydrate source, and inclusion of sodium bicarbonate on the diet selections of sheep.

Abstract: We proposed an hypothesis that ruminants attempt to select a diet that promotes high levels of feed intake by maintaining optimal ruminal conditions. Three tests of the hypothesis considered whether the diet selection of sheep given either a choice of two high energy density (ED) feeds or a choice between a high and a low ED feed is affected by 1) sodium bicarbonate inclusion (NaHCO3; 1, 2, and 4% [wt/wt]) in the high [ED] feed); 2) dietary carbohydrate source (barley-based, B and sugar beet/ barley, S) of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
39
3

Year Published

2002
2002
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 37 publications
3
39
3
Order By: Relevance
“…This high intake can produce digestive disorders such as ruminal acidosis Gaebe et al, 1998;Bodas et al, 2006) and it has been suggested that high levels of rumen degradable protein in the diet might help maintain a higher ruminal pH (Van Soest, 1994). This feeding behaviour is in agreement with evidence suggesting that the objective of sheep, when selecting diets, is to achieve a high nutrient intake while maintaining a stable ruminal environment (Cooper et al, 1996;James et al, 2002).…”
Section: Discussionsupporting
confidence: 89%
“…This high intake can produce digestive disorders such as ruminal acidosis Gaebe et al, 1998;Bodas et al, 2006) and it has been suggested that high levels of rumen degradable protein in the diet might help maintain a higher ruminal pH (Van Soest, 1994). This feeding behaviour is in agreement with evidence suggesting that the objective of sheep, when selecting diets, is to achieve a high nutrient intake while maintaining a stable ruminal environment (Cooper et al, 1996;James et al, 2002).…”
Section: Discussionsupporting
confidence: 89%
“…In the literature, the studies on choices between forages of different quality are relative to only one difference in quality, that is in choice trials between rye-grass and clover [1,21,23] or between vegetative and reproductive swards [6], or when one of the two forages is pelleted [3,18].…”
Section: Introductionmentioning
confidence: 99%
“…When the relative intake rates (IR) and choices are measured without a constraint, choices are usually recorded in short-term tests [13,17,21]. However, measurements over several days are assumed to take better account of the post-ingestive effects of individual foods that influence choice [3,11].…”
Section: Introductionmentioning
confidence: 99%
“…Insufficient adaptation to diet may result in disintegration of the epithelium (22), translocation of lipopolysaccharides (30), and disturbed transport mechanisms (22) and can further cause subacute ruminal acidosis (14, 49). This disease not only can lead to depressed feed intake and milk production, but can also be associated with laminitis, inflammation, and liver abscesses (14,42,49).Hence, one objective of attaining an adequate diet composition for ruminants is to maintain the physiological functions of the forestomach, such as optimal fermentation and absorptive properties (15,20). The phenotypic effects of diets, particularly of concentrate supplementation on rumen morphology and physiology, have been well investigated (38, 55) and reviewed (7).…”
mentioning
confidence: 99%
“…Hence, one objective of attaining an adequate diet composition for ruminants is to maintain the physiological functions of the forestomach, such as optimal fermentation and absorptive properties (15,20). The phenotypic effects of diets, particularly of concentrate supplementation on rumen morphology and physiology, have been well investigated (38, 55) and reviewed (7).…”
mentioning
confidence: 99%